The Ugly Side of Colchicine - Justin Cozza MD; Tuong Vi Cassandra Do DO; Shyam Ganti MD; Jayaramakrishna Depa MD (SAGE Publishing, 2021)
We report a rare case of a 32-year-old male who ingested 32.4 to 54 mg of colchicine and presented after 44 hours. He developed progressive multiple organ failure with shock, acute kidney failure, troponemia, pancytopenia, absolute neutropenia, disseminated intravascular coagulation, acute liver failure, rhabdomyolysis, and lactic acidosis. He also developed electrolyte abnormalities and refractory hypoglycemia. Initial treatment consisted of activated charcoal, fluids, and broad-spectrum antibiotics with supportive treatment of mechanical ventilation, hemodialysis, vasopressors, N-acetylcysteine, colony-stimulating factors, and blood products. Literature shows potential benefit of colchicine-specific Fab fragments for acute toxicity with limited studies and is not currently available in the United States. Further research for N-acetylcysteine protocol for acute liver failure in colchicine toxicity and potential use of colchicine-specific Fab fragments is needed. Our case demonstrates the importance of early use of activated charcoal for ingestion overdose with the incorporation of poison control into multidisciplinary team for coordinated patient care.